Pengaruh Model Pembelajaran RADEC berbasis STEAM terhadap Literasi Sains Siswa Kelas IV Sekolah Dasar - Cindy Amalia Putri; Zulfadewina Zulfadewina (Jurnal Elementaria Edukasia, 2023)
The low level of science literacy among students encourages this research because there is a need for learning that can relate science to everyday phenomena. This study aims to determine the effect of the STEAM-based RADEC learning model on the science literacy of fourth grade elementary school students. This study used a quasi-experimental design with a post-test only control group design. A random sampling technique was used to take a sample consisting of 51 students: 27 students in the experimental class and 24 students in the control class. A multiple choice test with 20 items is used to measure students' science literacy abilities. The results of the test data collection were then calculated and analyzed using the t-test formula with the help of the SPSS version 26 program. The results of the hypothesis test showed a significance value of 0.000 <0.05, so H1 was accepted, which means that there was a significant influence between students who were taught with the STEAM-based RADEC learning model and students who were not taught with the STEAM-based RADEC learning model. The mean post-test for science literacy in the experimental class was 88, which was 78 for the control class. This means that the STEAM-based RADEC learning model has a significant effect on the science literacy of fourth grade elementary school students.